Alternativa didáctica “Talleres ambientales” y su influencia en la conducta ecológica en niños y niñas de educación primaria de la I.E 00537 Matilde del Águila - Cabrera Arista, David (2010)
the present work of investigation raises the didactic alternative "ENVIRONMENTAL FACTORIES" in order to obtain a change of significant conduct in the students of primary education in the group of students of the sixth "B" in the Curricular area of Science Technology and Atmosphere of the l. E. Matilde Of the Eagle Velasquez of the city of La Rioja in 2009. The hypothesis that is formulated is: lf it influences of significant way in the development of an environmental conduct in the group of students of the sixth "B" who worked with the didactic alternative "ENVIRONMENTAL FACTOR/ES" with respect to the group of students of the síxth "C" in whích not she applíed this alternative to him. The study population was confirmed by 44 students of the sixth degree. The sample selected for the study was of 21 students, assigned of no probabilistic way, being the totality of students of section "C" (Group control) and section "B" (experimental Group). In conclusion the didactic alternative "ENVIRONMENTAL FACTORIES" has significantly improved (as much statistical as pedagogically and didactically) the environmental conservacionista conduct in the students.